Factors impacting lipid digestion and nutraceutical bioaccessibility assessed by standardized gastrointestinal model (INFOGEST): Emulsifier type. (November 2020) - Tan, Yunbing; Zhang, Zhiyun; Muriel Mundo, Jorge; McClements, David Julian
Graphical abstract: Highlights: INFOGEST model used to study food matrix effects on digestion and bioaccessibility. Lysolecithin, caseinate, quillaja saponin, gum arabic, and Tween 20 as emulsifiers. Lysolecithin and caseinate gave slowest lipid digestion and Tween 20 the fastest. Emulsions with lysolecithin gave lowest bioaccessibility and Tween 20 the highest. Abstract: This paper is part of a series examining the impact of the main factors influencing lipid digestion and nutraceutical bioaccessibility in β-carotene-loaded oil-in-water emulsions using the harmonized INFOGEST simulated gastrointestinal model. Here, the impact of emulsifier type was examined since food emulsions and nutraceutical delivery systems are often stabilized by various types of emulsifier. The INFOGEST method was adopted to investigate the in vitro gastrointestinal fate of emulsions stabilized by five kinds of food-grade emulsifier representing different classes: synthetic surfactants (Tween 20); natural surfactants (quillaja saponin); proteins (caseinate); polysaccharides (gum arabic); and phospholipids (soy lysolecithin). Microfluidization produced emulsions with small droplet sizes for all emulsifiers, except soy lysolecithin. Within the gastrointestinal model, the caseinate-coated oil droplets had the worst gastric stability, with severe droplet flocculation and coalescence occurring in the stomach. The fraction of the lipid phase that had been digested by the end of the gastrointestinal model was considerably lower for the emulsions stabilized by soy lysolecithin (93%) or caseinate (93%), than those stabilized by gum arabic (99%), quillaja saponin (111%) or Tween 20 (117%). This effect was attributed to lower surface area of lipids available for lipase to attach to for the lysolecithin and caseinate emulsions. The overall bioaccessibility of the β-carotene increased in this order: lysolecithin (25%) < gum arabic (51%) < caseinate (55%) < quillaja saponin (56%) < Tween 20 (62%). The impact of emulsifier type on carotenoid bioaccessibility was ascribed to various factors: (i) some emulsifiers inhibited lipid digestion and so a fraction of the β-carotene remained inside the undigested droplets and the mixed micelle phase had less solubilization capacity, i.e., lysolecithin, and caseinate; (ii) some emulsifiers protected β-carotene from chemical degradation, i.e., lysolecithin and caseinate; and (iii) some emulsifiers promoted sedimentation of the β-carotene-loaded micelles, i.e., lysolecithin. These results suggest that food emulsion behavior in the human gut may be influenced by the nature of the emulsifier employed, which is important knowledge when creating functional food and beverage products.